210 Clinical and ultrasound characteristics of neuroendocrine tumors of gynaecologic tract. (13th November 2020) - Quagliozzi, L; Iannantuono, C; Moro, F; Mascilini, F; Pozzati, F; Ciccarone, F; Biscione, A; Scambia, G; Testa, AC
Abstract : Introduction: To identifying clinical and ultrasound features of Neuroendocrine neoplasia (NEN) of the gynecologic tract. Methods: Retrospective study. Clinical and ultrasound characteristics of patients with histological diagnosis of NENs of the gynecologic tract from January 2015 to November 2019 were described. One author reviewed ultrasound images and described them using pattern recognition. Results: 50 patients were included. The median age was 52 (14–93) years. Thirty-nine (78%) were symptomatic, the most common symptom was vaginal bleeding (in 21/50, 54%). At ultrasound examination, most primary ovarian NEN appeared as unilateral (9/10, 90%), purely solid (8/10, 80%) with moderate or rich vascularization (7/10, 70%). Most metastatic ovarian NENs were bilateral (10/15, 67%), purely solid (100%) with irregular margins (14/15, 93%) and rich vascularization (13/15, 87%). NENs of the cervix were most frequently hypoechoic solid tumor (7/15, 47%) with irregular margins in all cases and most of them were richly vascularized (9/15, 60%). NENs of the endometrium were hypoechoic solid mass in 3/8 (37%). All cases showed irregular margins and most of them (62%) were minimal vascularized. Pattern recognition revealed that in 90% of primary ovarian NENs anechoic areas were presented. About cervical NENs the typical image was a solid tumor presenting multiple hyperechoic spots. No typical ultrasound feature was observed for endometrial cancer. Conclusion: At ultrasound examination, both primary ovarian NENs and metastatic NENS to the ovary appear as irregular solid masses with moderate or rich vascularization. Cervical NENs appear as hypoechoic solid tumors, with irregular margins and highly vascularization and endometrial NENs are solid hypoechoic tumors with irregular margins.